Combating unethical publications in Iraqi higher education: A pre- and post-intervention programme assessment - Haneen A. Haleem; Kadhum, Mohammed (Malaysian Journal of Library and Information Science, 2025)
This study examines the Responsible Publishing Initiative (RPI), a new intervention programme developed under University of Babylon’s academic research policy to combat unethical publishing among research students by addressing predatory or hijacked journals. The study aims to: i) examine the awareness and practise of scholarly publishing among research students before and after participation in the new intervention programme; ii) analyse the publication data of research students before and after participation in the new intervention programme. The results show that at least 37 per cent of students have published in predatory journals. After participating in the RPI programme, it was found that students’ awareness had increased and the number of publications in predatory journals had decreased significantly. The initial success of the programme demonstrates the importance of educational interventions to promote academic integrity. The study also emphasises the need for continuous monitoring and evaluation to ensure the long-term effectiveness of the newly proposed initiative. This research contributes to the broader academic discourse on sustainable development and is in line with UN SDG Goal 4 (Quality Education) and Goal 16 (Peace, Justice and Strong Institutions) by promoting a culture of integrity and rigour in Iraq’s academic publishing landscape.